Δ12 fatty acid desaturase gene from Geotrichum candidum in cheese: molecular cloning and functional characterization - Luo, Xue (FEBS Open Bio, 2018)
Soft cheese with white rind lacks essential fatty acids (EFAs), and as a result its long‐term consumption may lead to various kinds of cardiovascular and cerebrovascular diseases, such as hyperlipidemia, hypertension, and atherosclerosis. Geotrichum candidum is a dimorphic yeast that plays an important role in the ripening of mold cheese. A gene coding for Δ12 fatty acid desaturase, a critical bifunctional enzyme desaturating oleic acid (OA) and linoleic acid (LA) to produce LA and α‐linolenic acid (ALA), respectively, was isolated from G. candidum, and then cloned and heterologously expressed in Saccharomyces cerevisiae. This gene, named GcFADS12, had an open reading frame of 1257 bp and codes for a protein of 419 amino acids with a predicted molecular mass of 47.5 kDa. Characterization showed that GcFADS12 had the ability to convert OA to LA and LA to ALA, and the conversion rates for OA and LA were 20.40 ± 0.66% and 6.40 ± 0.57%, respectively. We also found that the protein product of GcFADS12 catalyzes the conversion of the intermediate product (LA) to ALA by addition of OA as the sole substrate. The catalytic activity of GcFADS12 on OA and LA was unaffected by fatty acid concentrations. Kinetic analysis revealed that GcFADS12 had stronger affinity for the OA than for the LA substrate. This study offers a solid basis for improving the production of EFAs by G. candidum in cheese.